The impact of concomitant chronic total occlusion on clinical outcomes in patients undergoing transcatheter aortic valve replacement: a large single-center analysis - Will, Maximilian; Schwarz, Konstantin; Weiss, Thomas; Leibundgut, Gregor; Schmidt, Elisabeth; Vock, Paul; Mousavi, Roya; Borovac, Josip A.; Kwok, Chun Shing; Hoppe, Uta C.; Mascherbauer, Julia; Lamm, Gudrun (Frontiers in Cardiovascular Medicine, 2024)
Background: Coronary artery disease (CAD) is a common finding in patients with severe aortic stenosis undergoing transcatheter aortic valve replacement (TAVR). However, the impact on prognosis of chronic total occlusions (CTOs), a drastic expression of CAD, remains unclear.We retrospectively reviewed 1487 consecutive TAVR cases performed at a single tertiary care medical center. Pre-TAVR angiograms were analyzed for the presence of a CTO. At the time of TAVR, 11.2% (n = 167) patients had a CTO. There was no significant association between the presence of a CTO and in-hospital or 30-day mortality. There was also no difference in long-term survival. LV ejection fraction and mean aortic gradients were lower in the CTO group.TAVR differ in their risk profile and clinical findings to patients without CTO. CTO lesion per se were not associated with increased mortality, nevertheless CTOs which supply non-viable myocardium in TAVR population were associated with increased risk of death. Additional research is needed to evaluate the prognostic significance of CTO lesions in TAVR patients.Coronary artery disease (CAD), aortic stenosis (AS), transcatheter aortic valve replacement (TAVR), chronic total occlusion (CTO), percutaneous coronary intervention (PCI).